Sweet love - Strohmeyer, Sarah (Dutton, 2008)
Julie Mueller, once a brilliant local television reporter, has been fired for the sin of being forty. Broke, divorced, unemployed, and struggling to raise a teenage daughter alone, she had given up on happiness until she receives for Mother's Day four dessert classes that spark not only a new burst of culinary creativity but a burning passion for one of her fellow students, Michael Slayton, a true love she let slip away.--From publisher description.